Penguatan Kelembagaan Melalui Ekonomi Digital Pada Kelompok Usaha Kue Basah di Desa Dangin Puri Kaja Denpasar Bali - Ni Nengah Seri Ekayani; Ni Made Mahendrawati; Ni Nyoman Rusmiati; Ni Wayan Sitiari (Universitas Warmadewa, 2024)
The development of tourism in Bali requires support from various sectors. Home industry in the culinary sector is one of the sectors that contributes to community income. The home industry of wet cakes, Balinese snacks, is one of the cake products that is widely produced by PKK mothers in Dangin Puri Kaja Village in Denpasar. However, the development of the home industry business faces various obstacles. Therefore, the involvement of the government, community and stakeholders is needed to support the development of the home industry. The purpose of this service is the importance of marketing strategies with a digital marketing mix, production techniques to create unique products and the importance of having halal/sukla certificates.Data was collected using observation and interviews, lectures/counseling, mentoring and simulations. The analysis technique uses a descriptive method. The results show that the wet cake business group in Banjar Buana Sari, Dangin Puri Kaja Village, East Denpasar, really needs a deep understanding of the role of the digital economy in strengthening MSME institutions and assistance related to digital marketing, competitive products and accounting systems. Therefore, it is necessary to provide lectures, consistent and continuous assistance related to the recording system, online marketing system, how to produce efficiently and effectively and products need to be equipped with halal/sukla certificates.